2017
DOI: 10.1007/s00423-017-1549-x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of parathyroid adenomas using 11C-methionine pet after prior inconclusive imaging

Abstract: PurposeMinimally invasive parathyroidectomy (MIP) is the recommended treatment in primary hyperparathyroidism (pHPT) for which accurate preoperative localization is essential. The current imaging standard consists of cervical ultrasonography (cUS) and MIBI-SPECT/CT. 11C-MET PET/CT has a higher resolution than MIBI-SPECT/CT. The aim of this study was to determine the diagnostic performance of 11C-MET PET/CT after initial inconclusive or negative localization.MethodsWe performed a retrospective single center coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…In previous studies, 11 C-methionine has been shown to be of great value, especially, but not only, in the setting of negative 99m Tc-sestamibi results (14)(15)(16)(17). The pooled sensitivity in a metaanalysis of 9 studies with a total of 137 patients was found to be 86% (24).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies, 11 C-methionine has been shown to be of great value, especially, but not only, in the setting of negative 99m Tc-sestamibi results (14)(15)(16)(17). The pooled sensitivity in a metaanalysis of 9 studies with a total of 137 patients was found to be 86% (24).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, problems arise if neither imaging modality can locate the PTA or if the results obtained by imaging are inconclusive or discordant. 11 C-methionine PET/CT has been successfully applied in this setting (14)(15)(16)(17)(18). During the last few years, radiolabeled choline has been increasingly used to localize PTAs, with high sensitivities reported (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…13 ZT can also be confused with a parathyroid adenoma, especially in patients with primary hyperparathyroidism. In a previous report reviewing primary hyperparathyroidism, 25 there were some cases in which the findings of a diagnostic imaging study such as [ 11 C]methionine PET/CT were positive but the surgeon could not locate the adenoma during the operation. We believe that some of these cases might have resulted from confusion of the ZTs with parathyroid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, new functional imaging techniques using positron emission tomography (PET)/CT, with, e.g., 11 C-methionine [8, 9] as radiotracer, have been studied, but no ideal PET tracer for adenomas has emerged so far. Recently, 11 C/ 18 F-choline was reported for visualization of adenomas and favorable results have been published in literature [1015].…”
Section: Introductionmentioning
confidence: 99%